Vliv charakteristik tlumiče na jízdní dynamiku - Nguyen, Michal (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2018)
Táto práca sa zaoberá skúmaním charakteristík tlmiča a vplyvom jednotlivých parametrov na dynamiku jazdy automobilu, predovšetkým za využitia výpočetného programu Matlab Simulink.

This thesis deals with the examination of damper characteristics and influence of individual parameters on vehicle handling, primarily with the use of computer program Matlab Simulink.
Influence of Damper Characteristics on Vehicle Handling
Keywords: štvrtinový model automobilu; charakteristika tlmiča; Matlab; diplomová práca; quarter car model; damper characteristics; Matlab; master's thesis